Bioligical features of sedentary and migratory roedeer of Sumy region - Омельченко, Г. О. (Scientific Progress & Innovations, 2017)
In Sumy region, the divergence of the Capreolus capreolus population is growing at 2 subpopulations: sedentary and migratory. This is due to the geographical dissociation of them during the period of gossip and the difference between the natural and climatic and biogeochemical conditions of their places of residence during the snowy period of the year. The sedentary and migratory roe deer are statistically significant (p≤0.05) differing in terms of size, slaughter weight, carcass weight, mortality rate, development of internal organs and hematological parameters. Migratory roe deer are more sedentary. In the unit volume of blood migratory roe more hemoglobin and erythrocytes are contained than in sedentary ones, however, the hemoglobin saturation of erythrocytes is higher in sedentary animals.